2009
DOI: 10.1002/adem.200900213
|View full text |Cite
|
Sign up to set email alerts
|

Three‐Dimensional Printing of Complex‐Shaped Alumina/Glass Composites

Abstract: Alumina/glass composites were fabricated by three‐dimensional printing (3DP™) and pressureless infiltration of lanthanum‐alumino‐silicate glass into sintered porous alumina preforms. The preforms were printed using an alumina/dextrin powder blend as a precursor material. They were sintered at 1600 °C for 2 h prior to glass infiltration at 1100 °C for 2 h. The influence of layer thickness and sample orientation within the building chamber of the 3D‐printer on microstructure, porosity, and mechanical properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 17 publications
0
44
0
Order By: Relevance
“…Polyamide (PA) specimens manufactured by SLS; three different configurations were manufactured with the purpose of evaluating the effect of building direction on Mode I fracture mechanic properties of the material. Similar studies on PA-Al2O3 composites have been presented by [5,6], mainly focused on tensile or bending properties. The novelty of this work lays in its focus on the fracture mechanics properties of PA for SLS, and on the investigation on the capability of AM processes to build 3D artificial cracks, otherwise impossible to create by classic methods.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Polyamide (PA) specimens manufactured by SLS; three different configurations were manufactured with the purpose of evaluating the effect of building direction on Mode I fracture mechanic properties of the material. Similar studies on PA-Al2O3 composites have been presented by [5,6], mainly focused on tensile or bending properties. The novelty of this work lays in its focus on the fracture mechanics properties of PA for SLS, and on the investigation on the capability of AM processes to build 3D artificial cracks, otherwise impossible to create by classic methods.…”
Section: Introductionmentioning
confidence: 82%
“…They also proposed a model where it is hypothesized that the layerby-layer construction is only marginally responsible for the anisotropic behavior of the material. Zhang et al [6] 3D printed alumina/glass composites, and investigated the effect of sample orientation within the building chamber on microstructure, porosity and mechanical properties of the final products. They showed that sintered samples orientated parallel to print head direction exhibit significantly higher fracture toughness than those printed in the other two orientations.…”
Section: Introductionmentioning
confidence: 99%
“…[58] In addition, the porosity is affected by maximized layer thickness: minimization of layer height could reduce the porosity to $19 vol%. [59] Powder bed stability can be optimized by moistening the powder during printing, resulting in enhanced surface roughness and geometric accuracy of the specimens. [60] Butscher et al [56] conducted a comprehensive study to relate the powder properties to printability.…”
Section: Three-dimensional Printing (3dp)mentioning
confidence: 99%
“…Not only tape-cast products exhibit an anisotropic microstructure; the shrinkage anisotropy could also be observed during the sintering of uniaxially pressed, extruded and threedimensional printed ceramics. [17][18][19] During uniaxial pressing, extrusion and tape casting, it was found that non-spherical ceramic particles can be textured and that the largest and smallest shrinkages occur in the directions perpendicular and parallel to the particle orientation direction, respectively. 17 During rapid prototyping based on layer-by-layer assemblies via 3D printing, elongated pores perpendicular to the thickness direction as well as a layered microstructure could be found.…”
Section: Introductionmentioning
confidence: 99%